Verificação estrutural das lajes da ponte de São Simão: um estudo de caso - Burmann, Rodrigo Possobon (2022)
Projects of reinforced concrete structures have always been important in the history of engineering. A good project aims not only at an adequate execution, avoiding cracks and the ruin of the structure, but also at optimizing the use of concrete and steel. In this sense, the present study sought to exemplify the calculation of the slab and the verification of the longitudinal shear between table and soul of the bean, of the São Simão bridge, executed in reinforced concrete in the city of Cacequi - RS. Such verification is provided for in Annex "E" of the new standard for bridges in reinforced concrete, ABNT NBR 7187, updated in 2021. Regarding the work methodology, efforts were calculated, the design for the ultimate limit state, verifications for the service limit state of the bridge slab in question and, after that, the verification of Annex “E”. The calculations were made with the aid of the Ftool program, UniCalcPro, FlexCisTor and electronic spreadsheets. At the end of the calculation, it was demonstrated that there is a need for special seam reinforcement for the bridge in question.